Countering MTV Influence in Indonesia and Malaysia - Seneviratne, Kalinga (Book collections on Project MUSE., 2012)
This book discusses three major elements - MTV, the Music of Malaysia, and the Music of Indonesia - and how these three interact in the modern cultural setting. The research objective behind the book was to study the impact of globalization, in the form of the MTV onslaught on the youth musical culture and identities of Indonesia and Malaysia, and to determine what theoretical basis could explain the new cultural products which have risen in response to this process. The book goes on to examine whether the nasyid and irama Malaysia music genres in Malaysia and dangdut in Indonesia are part of.